Analysis of expressed sequence tags from Gibberella zeae (anamorph Fusarium graminearum) - Trail, F.; Xu, J.R.; San Miguel, P.; Halgren, R.G; Kistler, H.G.
Gibberella zeae is a broad host range pathogen that infects many crop plants, including wheat and barley, and causes head blight and rot diseases throughout the world. To better understand fungal development and pathogenicity, we have generated 7996 ESTs from three cDNA libraries. Two libraries were generated from carbon-(C-)and nitrogen- (N-)starved mycelia and one library was generated from cultures of maturing perithecia (P). In other fungal pathogens, starvation conditions have been shown to act as cues to induce infection-related gene expression. To assign putative function to cDNAs, sequences were initially assembled using StackPack. The estimated total number of genes identified from the three EST databases was 2110: 1088 contigs and 1022 singleton sequences. These 2110 sequences were compared to a yeast protein sequence reference set and to the GenBank nonredundant database using BLASTX. Based on presumptive gene function identified by this process, we found that the two starved cultures had similar, but not identical, patterns of gene expression, whereas the developmental cultures were distinct in their pattern of expression. Of the three libraries, the perithecium library had the greatest percentage (46
Keywords: GIBBERELLA ZEAE; FUSARIUM GRAMINEARUM; MYCOTOXIN; DEOXYNIVALENOL; ZEARALENONE; PERITHECIA; ASCUS; PATHOGENICITY; VIRULENCE; EXPRESSED SEQUENCE TAGS